Siap: Pragmatic multifunctionality and register diffusion in Indonesian military and civilian discourse - Dhanan Abimanto; Wasi Sumarsono (Talenta Publisher, 2026)
The Indonesian word siap (literally: ready/prepared) functions far beyond its lexical meaning within Indonesian military and semi-military institutional discourse. This study investigates the pragmatic multifunctionality of siap as a discourse marker, speech act response token, and institutional affirmation signal, and examines its diffusion into civilian registers. Employing a descriptive qualitative approach grounded in Speech Act Theory, Pragmatic Markers Theory, and Register Diffusion Theory, this study analyzed a corpus of 240 naturally occurring utterances from three sources: audio-recorded institutional interactions at an Indonesian maritime education institution, digital communication data from social media platforms, and semi-structured interviews with twelve informants. Data were analyzed using Hymes' SPEAKING model. The findings reveal six distinct pragmatic functions of siap in military discourse, with hierarchical compliance marking as the most frequent function (35.4% of the military corpus): (1) hierarchical compliance marker, (2) epistemic acknowledgment token, (3) error-affirmation signal, (4) commissive speech act initiator, (5) phatic rapport marker, and (6) turn-taking regulator. In civilian contexts, siap undergoes pragmatic bleaching, splitting into two sub-functions: a professional affirmative and a casual phatic filler. The diffusion pathway is mediated by social media, military-themed entertainment, service industry adoption, and Indonesia's historical cultural proximity to military institutions.